An Event-Related Potential Study of the Neural Response to Inferred Motion in Visual Images of Varying Coherence - Lei Jia; Yufan Xu; John A. Sweeney; Cheng Wang; Billy Sung; Jun Wang (Frontiers in Psychology, 2019)
A vivid sense of motion can be inferred from static pictures of objects in motion. Like perception of real motion (RM), viewing photographs with implied motion (IM) can also activate the motion-sensitive visual cortex, including the middle temporal complex (hMT+) of the human extrastriate cortex. Moreover, extrastriate cortical activity also increases with motion coherence. Based on these previous findings, this study examined whether similar coherence level-dependent activity in motion-sensitive human extrastriate cortex is seen with IM stimuli of varying coherence. Photographic stimuli showing a human moving in four directions (left, right, toward, or away from the viewer) were presented to 15 participants. The coherence of the stimuli was manipulated by changing the percentage of pictures implying movement in one direction. Electroencephalographic data were collected while participants viewed IM or counterpart non-IM stimuli. The P2 response of extrastriate visual cortex (source located at hMT+) increased bilaterally with coherence level in the IM conditions but not in the non-IM conditions. This finding demonstrates that extrastriate visual cortical responses are progressively activated as motion coherence increases, even when motion is inferred, providing new support for the view that the activity of human motion-sensitive extrastriate visual cortex can be modulated by top-down perceptual influences in addition to its well-established role in processing bottom-up sensory signals.